2008
DOI: 10.1292/jvms.70.693
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Arginine Vasopressin and High Signal Intensity in the Pituitary Posterior Lobe on T1-Weighted MR Images in Dogs

Abstract: ABSTRACT. The posterior lobe of the pituitary gland (PL) normally shows characteristic high signal intensity (SI) on T1-weighted MR images (T1WI) in humans. The high SI is thought to represent storage of arginine vasopressin (AVP) in the PL. Normal dogs also show a high SI on T1WIs, but the origin is unclear. In the present study, we investigated whether the high SI in the PL on T1WIs in normal dogs is caused by AVP. We examined the SI in the PL on T1WIs, plasma AVP concentrations and plasma osmolality in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Additionally, MRI measurements of the pituitary can provide insight into vasopressin levels stored in its posterior lobe. On T1-weighted MRI the neurohypophysis (i.e., posterior lobe of the pituitary) is hyperintense (i.e., a bright spot), but the signal intensity diminishes after water deprivation (Lee et al, 2001) or infusion of hypertonic saline into the blood stream (Teshima et al, 2008). The neurohypophyseal signal intensity change corresponds to blood plasma levels of vasopressin (Lee et al, 2001; Teshima et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MRI measurements of the pituitary can provide insight into vasopressin levels stored in its posterior lobe. On T1-weighted MRI the neurohypophysis (i.e., posterior lobe of the pituitary) is hyperintense (i.e., a bright spot), but the signal intensity diminishes after water deprivation (Lee et al, 2001) or infusion of hypertonic saline into the blood stream (Teshima et al, 2008). The neurohypophyseal signal intensity change corresponds to blood plasma levels of vasopressin (Lee et al, 2001; Teshima et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this characteristically high signal intensity is markedly decreased by the depletion of AVP in disorders such as CDI [10,33,34]. In a previous study, we concluded that the high signal intensity in the posterior lobe in T1-weighted images in normal dogs was caused by AVP stored at the site, and there was a significant correlation between the plasma AVP concentrations and the SI ratio in the posterior lobe [37]. In this study, the SI ratio was significantly lower in the CA group than in the control group.…”
Section: Discussionmentioning
confidence: 80%
“…Plasma arginine vasopressin (AVP) concentrations were assayed using the radioimmunoassay (RIA) double antibody technique (AVP RIA Mitsubishi, Mitsubishi Kagaku Iatron, Tokyo, Japan), as described previously [37]. Before TSS, the blood samples for the assay were collected prior to MRI of the pituitary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PDH and control groups, the SI ratios of the posterior lobe were measured, as previously described [22]. The SI value was measured at the posterior lobe and the cerebral cortex by MRI computer software on the T1-weighted transverse MR images.…”
Section: Measurement Of the Si Ratio Of The Posterior Lobementioning
confidence: 99%